Static compression testing CFRP single-lap composited joints using X-ray μCT. (15th February 2020) - Zhang, Hongzhuang; Li, Changyou; Dai, Weibing; Liu, Yuzhuo; Tian, Sen; Huang, Wenchao; Jia, Dawei; He, David; Zhang, Yimin
Abstract: In this paper, the static compressive mechanical behaviors of carbon fiber reinforced composites (CFRP) single-lap bolted joints under anti-buckling test fixture were studied. Acoustic emission (AE) technology was used to monitor the damage evolution of specimens. X-ray micro-computed tomography (X-ray μCT) was used to evaluate the damage of CFRP single-lap bolted joints. The surface morphology of the holes was studied by field emission scanning electron microscopy (FESEM). An image processing and analyzing method was proposed, which allows the damage of the specimens to be accurately visualized, separated and quantified in 3D. The results show that X-ray μCT characterization technique greatly improves the ability to characterize the damage of CFRP single-lap bolted joints. The squeezing damage of the composite holes caused by the inclination of the bolt is an important factor affecting the bearing capacity of CFRP single-lap bolted joints.